Сказки: [в 2 томах] (Братья Гримм) - Гримм Вильгельм Карл (1991)
Экземпляры: ф.12 (2003) / Инвентарный номер: 46102 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Г 84 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-45